2001
DOI: 10.23986/afsci.5705
|View full text |Cite
|
Sign up to set email alerts
|

Weeds in spring cereal fields in Finland - a third survey

Abstract: A survey of weeds in spring cereal fields was conducted in 16 regions of southern and central Finland in [1997][1998][1999]. Data were collected from conventional and organic farms, both of which applied their normal cropping practices. A total of 690 fields were investigated by counting and weighing the weed species from ten sample quadrats 0.1 m 2 in size in late July -early August. Altogether 160 weed species were found, of which 134 were broad-leaved and 26 grass species. The total number of weed species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
3
40
2
1
Order By: Relevance
“…The first phase in this assessment was definition of the weed flora of Europe, which resulted in the list of 2220 species. The species number can be regarded as high in comparison with the 768 species reported earlier by Glemnitz et al (2006) or compared with those reported in national weed surveys, for example the 168 species from Finland (Salonen et al 2001) and 224 species from Denmark (Andreasen and Stryhn 2008). The high number of weed species in the European weed flora was partly due to inclusion of plant species occupying habitats other than agricultural ones (see Table 2), in contrast to previous studies.…”
Section: Discussioncontrasting
confidence: 41%
“…The first phase in this assessment was definition of the weed flora of Europe, which resulted in the list of 2220 species. The species number can be regarded as high in comparison with the 768 species reported earlier by Glemnitz et al (2006) or compared with those reported in national weed surveys, for example the 168 species from Finland (Salonen et al 2001) and 224 species from Denmark (Andreasen and Stryhn 2008). The high number of weed species in the European weed flora was partly due to inclusion of plant species occupying habitats other than agricultural ones (see Table 2), in contrast to previous studies.…”
Section: Discussioncontrasting
confidence: 41%
“…Our results are in accordance with previous studies conducted in the Mediterranean region, verifying always high weed diversity: 175 species in 138 surveys conducted by Cirujeda et al (2011) in Spain and 278 species in 86 surveys in Greece (Damanakis, 1983). These numbers are significantly higher compared with those found in the north and central Europe (Holzner and Immonen, 1982;Chancellor and FroudWilliam, 1984;Sutcliffe and Kay 2000;Salonen et al, 2001). The botanical families with greater representation were the same in both periods, and also with similar representation (of about 50%): Asteraceae followed by Poaceae and Fabaceae.…”
Section: Weed Vegetation Composition and Diversitymentioning
confidence: 79%
“…These numbers are much higher compared to those found in northern and central Europe, agreeing with Holzner & Immonen (1982), indicating that floristic diversity is higher in the Mediterranean areas. Thus, in central and southern England 46 species were recorded in 100 plots (Sutcliffe & Kay, 2000); in northern England, 87 species in 1,021 samples (Chancellor & Froud-William, 1984); and in Finland, 160 species in 690 plots (Salonen et al, 2001). On the other hand, Calha et al (2014a) have identified 43 weed species in maize, accounting for 21 families in Golegã, Ribatejo (Portugal).…”
Section: Resultsmentioning
confidence: 99%